2018
DOI: 10.3892/etm.2018.5875
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products inhibit the autophagy of renal tubular epithelial cells

Abstract: It is well known that autophagy serves a crucial role in renal tubular epithelial cell (RTEC) injury in the pathogenesis of chronic kidney disease (CKD). The accumulation of advanced oxidation protein products (AOPPs) also participates in the progression of CKD. However, the effects of AOPPs on autophagy remain unknown. To clarify the underlying mechanism of RTEC injury in CKD, the effect of AOPPs on HK-2 cells, an RTEC cell line, was investigated. The results of the present study revealed that AOPP exposure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Our previous study reported that AOPP inhibited RTEC autophagy and that autophagy inhibition induced RTEC injury (5). The present study revealed that hUC-MSCs enhanced AOPP-inhibited autophagy in HK-2 cells.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our previous study reported that AOPP inhibited RTEC autophagy and that autophagy inhibition induced RTEC injury (5). The present study revealed that hUC-MSCs enhanced AOPP-inhibited autophagy in HK-2 cells.…”
Section: Discussionsupporting
confidence: 62%
“…Dysregulated autophagy may occur in response to either intracellular or extracellular factors, such as endoplasmic reticulum stress, oxidative stress or pathogen infection (3,4). Consistent with those findings, our previous study revealed that advanced oxidation protein products (AOPP), a toxic protein product produced in patients with CKD, induced RTEC injury by inhibiting cell autophagy (5). Therefore, enhancing RTEC autophagy may suppress the progression of CKD.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thereafter, AOPPs are taken up by tubular cells via CD36, an AOPPs receptor. Zhang et al (34) reported that AOPPs stimulate mTOR signaling after being taken up via CD36 into HK-2 cells. This study shows that rapamycin, an mTOR inhibitor, suppresses the AOPPsinduced Elovl6 expression ( Figure 5C), suggesting that mTOR signaling contributes to Elovl6 induction by AOPPs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the basal activity of autophagy is inhibited in intrinsic cells in diabetic kidneys [ 104 ]. The potential mechanisms might be due to the appearance of oxidative stress and inflammation secondary to stimuli such as AGEs and urinary proteins [ 105 107 ]. Autophagy regulates TGF- β expression and suppresses kidney fibrosis through the autophagic degradation of mature TGF- β [ 108 ], which contributes to the occurrence of diabetic diffuse glomerulosclerosis and the excessive deposition of fibrotic materials in DN [ 109 ].…”
Section: Main Cellular and Molecular Mechanisms Of Accelerated Kidmentioning
confidence: 99%